PENGARUH JENIS PEKERJAAN DENGAN KETIDAK AKTIFAN IBU BERKUNJUNG KE POSYANDU DESA JALEN KECAMATAN BALONG KABUPATEN PONOROGO - Ambika Kurnia Mustikawati (Akbid Harapan Mulya Ponorogo, 2019)
Based on the Register Cohort weighing a toddler on November 10, 2018 at Posyandu Jalen there are 65 men mother toddler retrieved 25 (38.4%) bringing his son to the always active and 40 posyandu (61.6%) mother toddler people not actively bring his son to the Posyandu. A preliminary study of 10 people who are not active toddler's mother obtained work mother who brings her son off to their busy work posyandu 3 (30%) as civil servants, 3 (30%) as farmers and 4 (40%) as a trader. Type of this research is quantitative approach to koresional and use the form of cross sectional. The sample was all mother toddler who came to the village of posyandu Jalen Subdistrict Balong Ponorogo in January 2019 with the inclusion criteria and are taken using the technique of accidental sampling. The instruments used in this study using questionnaire. Analysis of the influence between the variable using the correlation test chi square with 0.05 significant level. The work of mothers in the village of Posyandu Jalen Subdistrict Balong Ponorogo almost half of the respondents i.e. as many as 25 (38.4%) working as the IRT and as many as 20 (30.9%) working as a trader. The aktifan visit the mother of most of the respondents (58.5%) i.e., 38. There is the influence of the type of work with the inactivity of the mother paid a visit to the village of posyandu Jalen Subdistrict Balong Ponorogo with statistical test p = 0.000. The kind of work that is most influential Working Moms as traders who are all as many as 20 respondents (100%) and mother working as CIVIL SERVANTS who are all as many as 7 respondents (100%) not active in the visit of the posyandu. Solutions carried out visits to posyandu on the schedule set by the posyandu and liveliness for a visit should arise on the mother because the toddler is a define in time is growing important role, will happen a whole person, due to his physical growth aspects have first gained attention as well as conduct posyandu cadre in order to approach with entwined good cooperation.